2022
DOI: 10.1007/s10549-022-06563-x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of long-term breast cancer survivors to follow-up care guidelines: a study based on real-world data from the SURBCAN cohort

Abstract: Purpose To identify adherence to follow-up recommendations in long-term breast cancer survivors (LTBCS) of the SURBCAN cohort and to identify its determinants, using real-world data. Methods We conducted a retrospective study using electronic health records from 2012 to 2016 of women diagnosed with incident breast cancer in Spain between 2000 and 2006 and surviving at least 5 years. Adherence to basic follow-up recommendations, adherence according to risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Several studies are promoted on the development of "patient-centered medical homes" whose philosophy is based on primary care patient-centered, complete, teambased, coordinated, accessible and focused on quality and safety [119]. Different players should be involved and considered, including in first place general practitioners (GPs), psychologists and specialists in oncological field (i.e., medical and radiation oncologists, nurse, case manager) [120,121]. The approach to the patient should be multidimensional to take into consideration not only the survivor as a patient within programs aimed at the early diagnosis of disease recurrence but above the person, as entirety, and his family network.…”
Section: Multidisciplinary Team To Address Breast Cancer Survivor Needsmentioning
confidence: 99%
“…Several studies are promoted on the development of "patient-centered medical homes" whose philosophy is based on primary care patient-centered, complete, teambased, coordinated, accessible and focused on quality and safety [119]. Different players should be involved and considered, including in first place general practitioners (GPs), psychologists and specialists in oncological field (i.e., medical and radiation oncologists, nurse, case manager) [120,121]. The approach to the patient should be multidimensional to take into consideration not only the survivor as a patient within programs aimed at the early diagnosis of disease recurrence but above the person, as entirety, and his family network.…”
Section: Multidisciplinary Team To Address Breast Cancer Survivor Needsmentioning
confidence: 99%
“…In breast cancer patients, Ouyang et al [24] reported a loss to follow-up rate of 12.9% (198/1536 patients) in the frst year and 26.8% (411/1536 patients) in the ffth year after surgery. Santiá et al [9] reported a similar loss to follow-up rate of 19% (37/194 patients) after the 6th year, which increased to 30% (97/326 patients) after the 16th year. Possible countermeasures include the use of reminder intervention to improve adherence to appointments, such as postradiotherapy follow-up [9,[22][23][24][25].…”
Section: Discussionmentioning
confidence: 83%
“…Santiá et al [9] reported a similar loss to follow-up rate of 19% (37/194 patients) after the 6th year, which increased to 30% (97/326 patients) after the 16th year. Possible countermeasures include the use of reminder intervention to improve adherence to appointments, such as postradiotherapy follow-up [9,[22][23][24][25]. In a cross-sectional study, Bruns et al [25] demonstrated that reminder intervention in breast cancer patients resulted in signifcantly higher rates of attendance at postradiotherapy follow-up; specifcally, he reported an absolute decrease in nonattendance from about 24% to 18% after written (postal) reminders and from about 24% to 9% after telephone reminders.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation